Kajian Dampak Proyek Jalan Tol Solo-Yogyakarta Terhadap Peforma Simpang Bersinyal Kronggahan Kota Yogyakarta - Hernawan Bachtiar Ramadhan; Fithri Estikhamah; Achmad Dzulfiqar Alfiansyah (Jurnal Civil Engineering Study, 2025)
The construction of the Solo-Yogyakarta-NYIA Kulon Progo Toll Road is expected to improve regional connectivity, but it also creates the potential for congestion at signalized intersections, such as Kronggahan Intersection. This study was conducted to evaluate the impact of toll road construction on the traffic performance of the intersection, using the Indonesian Road Capacity Guidelines (PKJI) 2023 method. Data was collected through traffic surveys in the morning and evening peak hours on four different days, then analyzed for existing conditions, road median change scenarios, and five-year projections. The results showed that the existing condition had an average degree of saturation (DJ) of 0.96 with a total delay of 112,578 seconds/smp. Changes to the road median due to toll construction increased the DJ to an average of 1.19 and the total delay jumped to 591,425 seconds/smp, accompanied by queue lengths of up to 403.65 meters. Simulation of the implementation of two phases without right turns succeeded in reducing the DJ to 0.32-0.39 and the delay to 2,448-6,754 seconds/smp. However, projections for 2030 show the DJ rising again to 1.13 due to growth in vehicle volumes. These findings emphasize the importance of adjusting geometric design and traffic management from the planning stage of toll projects so that infrastructure development can improve accessibility without causing significant congestion at local intersections. This research contributes to the development of civil engineering science, especially in the field of traffic management.